2010
DOI: 10.1163/016942409x12561252292422
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Spreading of Polar Liquids on Offset Papers

Abstract: The aim of this study was to investigate the spreading of sessile drops of polar probe liquids (water and ethylene glycol) on pigment coated offset papers. Furthermore, existing theoretical models for spreading were applied to evaluate the experimental results. The hydrodynamic model gave a better fit to the results at lower spreading rates, while the molecular-kinetic theory gave a good fit over a larger velocity range. Factors introduced to correct for the exponential dependency on time of the drop base radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The polymer dispersion will more easily penetrate the pores of the substrate reducing the amount of air/moisture entrapped, in both the substrate and inner layer of the coating, which will then result in less popping defects. 42 , 43 We can, however, not rule out the possibility that the presence of IPA could also have other effects that play a role in the film formation such as a plasticizing effect or acting as a coalescence aid. 40 , 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…The polymer dispersion will more easily penetrate the pores of the substrate reducing the amount of air/moisture entrapped, in both the substrate and inner layer of the coating, which will then result in less popping defects. 42 , 43 We can, however, not rule out the possibility that the presence of IPA could also have other effects that play a role in the film formation such as a plasticizing effect or acting as a coalescence aid. 40 , 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…The roughness, represented by drop base radius expansion, and the chemistry, represented by the contact angle, seem to be interrelated in the same way. For a larger data set [8] it was found that the correction coefficients do not agree with the trend of the RMS roughness, PPS values, or the Wenzel r-factor. The best correlation was found between the correction constants and the acid and base components.…”
Section: Comparison Of Modelsmentioning
confidence: 87%
“…The best correlation was found between the correction constants and the acid and base components. The correction coefficient seems to increase with increasing acid component σ A and decreasing base component σ B [8].…”
Section: Comparison Of Modelsmentioning
confidence: 89%
See 2 more Smart Citations